Effectiveness of a Domestic Abuse Program for Australian Indigenous Offenders. (December 2020) - Blatch, Chris; O'Sullivan, Kevin; Goodman-Delahunty, Jane; Willis, Matthew; Delaney, Jordan J.
The subject of this study is to assess the effectiveness of a culture-neutral domestic abuse program (DAP) developed for offenders with domestic and family violence histories, when used for Australian Indigenous offenders, serving community-based supervised orders. The study employed a retrospective quasi-experimental research design and intention-to-treat program definition for 953 DAP-treated men and propensity score–matched controls, from diverse cultural, religious, and racial backgrounds, 19% being Indigenous Australians. Outcomes measured were program completion, time to first reconviction, and reconviction rates. Indigenous men completed the program similar to non-Indigenous men (58% vs. 63%; NS), although significantly more dropped out (22% vs. 18%); 63% of Indigenous DAP-treated men, remained reconviction free versus 49% of Indigenous controls. Significant therapeutic benefits required program completion, 73% Indigenous and 74% of non-Indigenous men remained reconviction free. Indigenous DAP participants, relative to controls, took significantly longer to first reconviction. Survival was associated with prior criminal histories, but not with rural or remote domiciles. Reconviction rates were predicted by Level of Service Inventory–Revised actuarial risk scores and by DAP completion, but not by Indigenous status. Program effect size was d = .477, mean reconvictions for Indigenous DAP enrollees being 50% lower than controls. Generic domestic violence interventions utilising evidence-based theoretical principles can be effective for Indigenous offenders, despite an absence of specific Indigenous cultural, or healing content, and delivery by Indigenous facilitators or Elders.